IMPROVING THE TENTH GRADERS’ READING COMPREHENSION USING ETR METHOD - Sari Purnama Sari (Didascein : Journal of English Education, 2020)
Reading comprehension  is the act of understanding of a text. It means that reader can understand the meaning, main idea, topic and summary of the text. Experience –Text – Relationship (ETR) is a strategy that draws on backgroud knowledge, prior knowledge and experience. The objective of this research were to find out whether or not there was any significant improvement in reading comprehension of narrative text by using ETR method, and to find out whether or not there was any significant difference in students’ reading comprehension of narrative text between thoso who were taught by using ETR method and those who were not. This research involved 70 students as the sample, chosen by using purposive sampling technique. There were two groups involved, experimental and control group. Each group consisted of 35 students. A reading test was used to obtain the data for pretest and post-test. The obtained data were analyzed by using Paired Sample T-test and Independent-Sample T-test. Based on Paired Sample T-test, it was found that there was significant improvement on experimental students’ reading comprehension. Furthermore, based on the Independent Sample T-test, it was found that there was significant difference on reading comprehension between the students who were taught by using ETR method and those who were not.Keywords: reading comprehension, tenth graders, ETR method